2022
DOI: 10.56748/ejse.2225701
|View full text |Cite
|
Sign up to set email alerts
|

Durability of polypropylene fiber reinforced concrete: Literatures review

Abstract: Use of polypropylene fibers to reinforce concrete has attracted widespread attention from both researchers and construction industry because of the numerous characteristics they have, compared to other types of fibers. This paper critically reviews the current state of knowledge of impacting the inclusion of polypropylene fibers on concrete durability. Detailed review on the different durability properties including: Water and gas permeability, sorptivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…In Ref. (11) , Abdulkareem M et al ( 2022) reviewed the durability of propylene fibre-reinforced concrete. The authors reported that the incorporation of polypropylene fibres at various rates into the concrete can limit the development of cracks by forming a bond bridge, modifying the pore network, and thus enhancing durability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Ref. (11) , Abdulkareem M et al ( 2022) reviewed the durability of propylene fibre-reinforced concrete. The authors reported that the incorporation of polypropylene fibres at various rates into the concrete can limit the development of cracks by forming a bond bridge, modifying the pore network, and thus enhancing durability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among these, PPF concrete is a new type of composite material that improves toughness and fire resistance by adding fibers. It is less brittle than ordinary concrete and widely used in various civil and commercial buildings due to its simplicity of construction and affordability [1][2][3]. The frequent occurrence of fire incidents in recent years has caused significant harm to property and the safety of lives, and fires are recognized as major dangerous disasters.…”
Section: Introductionmentioning
confidence: 99%